HartWacht telemonitoring effectively reduces blood pressure in a real-life setting. (25th November 2020) - Abeln, B.G.S; Blok, S; Van Den Born, B.J; Somsen, G.A; Tulevski, I.I; Winter, M.M
Abstract: Introduction: Telemedicine platforms have the potential to reduce costs and improve outcomes in blood pressure reduction. Although results in the literature are promising, evidence remains limited and few home monitoring programs have successfully been integrated into daily clinical practice. The HartWacht home monitoring program is set-up for remote monitoring and treatment of patients with therapy resistant hypertension (systolic blood pressure>140 mmHg and >1 antihypertensive drugs). HartWacht is fully integrated into clinical care and is reimbursed by the majority of Dutch healthcare insurers. Purpose: The purpose of this study is to evaluate the effectiveness of the HartWacht program in blood pressure treatment in a real-life setting, and evaluate the number of interventions necessary to reach normotension. Methods: In this single center retrospective cohort study, we included all patients with therapy resistant hypertension that were included in the HartWacht program by their treating physician. At baseline, all patients measure blood pressure twice a day for the duration of one week, after which blood pressure measurements were performed once a week. Two pre-set alarms informed a team of designate nurses if blood pressures exceeded 140/90 mmHg (orange alarm) or 180/110 mmHg (red alarm). After one red or two successive orange alarms, the patient was contacted by telephone for guideline driven lifestyle advice or medication adjustment in consultation with a cardiologist. After every intervention, a blanking period of four weeks was set in which no orange alarms were visible. Results: The cohort consisted of 161 patients (mean age 63±9.8 years; 54% male). The median follow up time was 318 days. At baseline, the mean blood pressure was 155/91 mmHg. During follow-up mean blood pressure decreased significantly to 134/83 mmHg (p<0.001 for both systolic and diastolic blood pressure). At follow up, 102 (62%) patients were normotensive. During follow up participants received a mean of 0.46 lifestyle advices and 0.74 medication changes in 1.07 consultations. Conclusion: Home monitoring and treatment of patients therapy resistant hypertension with HartWacht resulted in a significant overall reduction of blood pressure, with >60% of patients being normotensive at last follow-up. Funding Acknowledgement: Type of funding source: None